Novel Selective Butyrylcholinesterase Inhibitors Incorporating Antioxidant Functionalities as Potential Bimodal Therapeutics for Alzheimer's Disease - GILMER, JOHN (My University, 2016)
sosorbide-2-carbamates-5-aryl esters are highly potent and very selective butyrylcholinesterase inhibitors. The objective of the present work was to address the hypothesis that the isosorbide-aryl-5-ester group could be replaced with an antioxidant functionality while maintaining inhibitor effects and selectivity. We successfully incorporated ferulic acid or lipoic acid groups producing potent selective inhibitors of butyrylcholinesterase (BuChE). The hybrid compounds were non-toxic to the murine hippocampal cell line HT-22 and lipoate esters were neuroprotective at 10 and 25 µM when the cells were challenged with glutamate (5 mM) in a similar manner to the positive control quercetin. The benzyl carbamate 7a was a potent inhibitor of BuChE (IC50 150 nM) and it was effective in reducing glutamate toxicity to neuronal cells at >5 µM. Representative compounds exhibited an antioxidant effect in the oxygen radical absorbance capacity assay as the lipoate 7d was not active, whereas the ferulate 8a showed a weak, but significant, activity with 0.635 ± 0.020 Trolox Equivalent.
PUBLISHED
Cited By :1 Export Date: 13 January 2017
Keywords: butyrylcholinesterase (BuChE).; butyrylcholinesterase (BuChE).